THE EFFECT OF REVENUE AND MARKET SEGMENTATION LEVEL TOWARDS VENTURE CAPITAL INVESTMENT IN MOBILE APPLICATION BUSINESS - Dennis Adrian; Riswan Efendi Tarigan (Bina Nusantara University, 2014)
The development of mobile applications has mushroomed in local and foreign industries. This provides a tremendous opportunity for developers. For technopreneur developer, the capital to run the business is one of the biggest problems despite the fact that they may have great competence in the field. The fact that the business has big potential market in Indonesia has invited investors from local and overseas to invest as venture capital. However, due to the lack of knowledge on building collaboration with the investors and on understanding the market and investor needs in a long term, the developer finds difficulties to grow its business and to compete with bigger competitors. The research intends to seek the influence in selecting the level of revenue and market segmentation to support the investment decisions in the business of mobile applications, so that the mobile application developer is able to monetize their business to attract investors to invest in the venture capital.